K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 12 2022

(2x - 3).7=35

2x - 3 = 5

2x = 8

2x = 23

ð  X = 3

23 tháng 12 2022

2x - 3).7=35

2x - 3 = 5

2= 8

2= 23

ð  X = 3

a: 9-25=7-x-(25+7)

=>7-x-25-7=-16

=>-x-25=-16

=>x+25=16

hay x=-9

b: \(10+2\left|x\right|=2\cdot\left(3^2-1\right)\)

\(\Leftrightarrow2\left|x\right|=2\cdot8-10=6\)

=>x=3 hoặc x=-3

c: -6x=18

nên x=18:(-6)=-3

9 tháng 12 2015

b. -6x=18

=> x = 18 : (-6)

=> x = -3

c. 35-3.|x|=5.(23-4)

=> 35-3.|x|=5.(8-4)

=> 35-3.|x|=5.4

=> 35-3.|x|=20

=> 3.|x|=35-20

=> 3.|x|=15

=> |x|=5

=> x \(\in\){-5; 5}

d. => 10+2.|x|=2.(9-1)

=> 10+2.|x|=2.8

=> 10+2.|x|=16

=> 2.|x|=16-10

=> 2.|x|=6

=> |x|=3

=> x \(\in\){-3; 3}

9 tháng 12 2015

a. 9 - 25 = ( 7 - x ) - ( 25 + 7 )

=> -16 = 7 - x - 32

=> x = 7 - 32 + 16

=> x = -9.

14 tháng 1 2018

a) 28 + 2x = 35 - (-13)

=> 28 + 2x = 48

=> 2x = 48 - 28

=> 2x = 20

=> x = 20 : 2

=> x = 10

Vậy x = 10

b) 2(x - 1)2 - 5 = 45

=> 2(x - 1)2 = 45 + 5

=> 2(x - 1)2 = 50

=> (x - 1)2 = 50 : 2

=> (x - 1)2 = 25

=> (x - 1)2 = 52

=> x - 1 = 5

=> x = 5 + 1 

=> x = 6

Vậy x = 6

14 tháng 1 2018

c) 20 - 3|x + 5| = -7

=> 3|x + 5| = 20 - (-7)

=> 3|x + 5| = 27

=> |x + 5| = 27 : 3

=> |x + 5| = 9

TH1: x + 5 = 9

=> x = 9 - 5 

=> x = 4

TH2: x + 5 = -9

=> x = -9 - 5

=> x = -14

Vậy x = 4 hoặc x = -14

15 tháng 12 2017

9-25=(7-x)-(25+7)

-16=7-x-32

7-x-32=16

7-x=-16+32

7-x=16 

x=16+7

x=23

B,35-3.|x|=5.(2^3-4)

35-3.x=5.(8-4)

35-3.x=5.4

35-3.x=20

3.x=35-20

3.x=15

X=15:3

x =5

C, -6x=18

-6.x=18

X=18:(-6)

X= -3

D,10+2.|x|=2.(3^2-1)

10+2.x=2.8

10+2.x=16

2.x=16-10

2.x =6

X=6:2

x=3

Ok k mk nha 

17 tháng 12 2017

a) 9 - 25 = ( 7 - x) - (25+7)

    - 16 =  7-x - 32

    7 - x - 32 = -16

   7 - x = -16 + 32

   7 - x = 16

      x = 16 + 7

      x = 23

b) -6x = 18

   - 6 .x = 18

        x = 18 : (-6)

       x = -3

 
 
24 tháng 9 2015

=> {x2-[36-(64-63)3-35]-15}3=1

=> [x2-(36-13-35)-15]3=1

=> [x2-(36-1-35)-15]3=1

=> (x2-0-15)3=13

=> x2-0-15=1

=> x2=1+15+0

=> x2=16

=> x2=42

vậy x=4.